TRANSFORMATION OF STATE POLICY IN THE FIELD OF PARTNERSHIP WITH SMALL AND MEDIUM BUSINESSES - CHORNII, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a thorough analysis of the current state of Ukraine's state policy in the field of partnership with small and medium-sized businesses (SMEs), which is a key segment of the national economy that ensures employment, innovative development and the formation of a competitive environment. The author focuses on the transformation processes taking place in the system of interaction between the state and the business sector, taking into account the challenges of war, economic instability, digital transformation and growing expectations from business. The main structural problems of SMEs are identified, among which insufficient access to financial resources, fragmented information support, uneven regional development and limited institutional capacity of authorities dominate. An assessment of existing state policy instruments, such as the program "Affordable Loans 5-7-9%", state guarantees, grant projects, consulting support, etc., is carried out from the standpoint of their accessibility, effectiveness and impact on the sustainability of SMEs. Based on a critical analysis of domestic and international practices, ways of modernizing state policy are proposed in the context of the development of public-private partnership, digitalization of communication processes, expansion of educational initiatives, transparency of support mechanisms and institutional strengthening of business infrastructure. Particular attention is paid to the need to build a partnership model of interaction between the state and SMEs, which involves decentralization of powers, active involvement of business associations in the policy-making process, strengthening of the analytical component and systematicity in decision-making. It is concluded that the transformation of state policy in the field of SMEs is a strategic direction that should be based on the principles of openness, inclusiveness and result orientation, and its successful implementation will be a key prerequisite for the recovery of the economy and ensuring its long-term competitiveness. The implementation of comprehensive measures aimed at simplifying the regulatory environment, expanding access to financing and supporting exports will contribute to the strengthening of SMEs and increasing their contribution to the national economy.
Keywords: state policy; small and medium-sized businesses; partnership; entrepreneurship support; Ukraine